2019
DOI: 10.1186/s12889-019-7233-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health behaviors and health outcomes among non-Hispanic Whites and Arab Americans in a population-based survey in California

Abstract: Background Few population-based studies of Arab American health behaviors and outcomes exist outside of Michigan. We aimed to provide prevalence estimates of health behaviors and outcomes for Arab Americans and compare them to non-Hispanic Whites in California. Methods We used data from the 2003–2016 California Health Interview Surveys. We determined Arab American ethnicity using an algorithm that considered place of birth of the respondent or parent and use of Arabic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…Preventive behavior among Arab Americans may be poor, especially for reducing infectious disease risk. Arab Americans are less likely to be vaccinated than the average American, and studies have found that they receive the influenza vaccine less frequently in the past year in California than white Americans, 4 which is corroborated by national data for influenza and pneumonia vaccinations. 24 This suggests the need for more targeted education about the risks of infectious diseases for this vulnerable subgroup, with a goal of positively influencing vaccination uptake.…”
Section: Preventive Behaviormentioning
confidence: 79%
See 2 more Smart Citations
“…Preventive behavior among Arab Americans may be poor, especially for reducing infectious disease risk. Arab Americans are less likely to be vaccinated than the average American, and studies have found that they receive the influenza vaccine less frequently in the past year in California than white Americans, 4 which is corroborated by national data for influenza and pneumonia vaccinations. 24 This suggests the need for more targeted education about the risks of infectious diseases for this vulnerable subgroup, with a goal of positively influencing vaccination uptake.…”
Section: Preventive Behaviormentioning
confidence: 79%
“…5 Researchers also found in a study among Arab Americans in California that the proportion of respondents who were overweight or obese was 55.2%. 4 These underlying health conditions are important risk factors for increased severity of COVID-19 and death in other groups and indicate increased risk for severity among Arab Americans.…”
Section: Underlying Health Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we analyzed data from the 2004-2016 CHIS survey cycles. More information on the CHIS can be found in previous work [15,16].…”
Section: Surveymentioning
confidence: 99%
“…As previously described, Arab Americans were identified using their responses to three questions on the CHIS Adult Questionnaire related to place of birth, language spoken at home, and parents' place of birth [15,16]. If one of 22 Arab League countries were indicated for participant's or parent's place of birth, then respondents were coded as Arab American.…”
Section: Study Populationmentioning
confidence: 99%